Making Thailand's services sector more competitive through international trade - Suzuki, Kosuke (OECD Economics Department Working Papers, 2020)
Services are an important part of global economic activity and of international trade. Nevertheless, compared to its very large tourism sector, the sector of high-end business services in Thailand remains small. As IT and information, and professional services are traded indirectly through value chains and are now crucial elements of manufacturing, strengthening these services would benefit Thailand in its post-COVID-19 participation of global value chains, enhancing the competitiveness of its manufacturers. This paper analyses how Thailand can seize the opportunity of growing international trade in services. It points out that liberalising services sector markets would strengthen the competitiveness of the services sectors and boost productivity not only in the sectors, but also in manufacturing sectors that rely on these services as input. In this regard, Thailand can benefit more from service-oriented Preferential Trade Agreements (PTAs). Moreover, eliminating FDI restrictions would not only be crucial to spur employment and exports, but also benefit consumers. The paper identifies that, to maximise the benefits of services trade integration, Thailand needs to step up policies to re- and up-skill workers and make the labour market more flexible